North American Unconventional Gas Conference and Exhibition 2011
DOI: 10.2118/144401-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design and Examination of Requirements for a Rigorous Shale-Gas Reservoir Simulator Compared to Current Shale-Gas Simulators

Abstract: The development of shale plays in North America has achieved great success in satisfying increased energy demand. With the advances in experimental approaches, investigation of microstructures in organic-rich shale has identified several different pore types and the abundance of pores from the nanometer to the micron scale. Yet current modeling work for such reservoirs is mainly performed with dual porosity models based on Darcy's law. In addition, a great discrepancy between simulation results and production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Knudson diffusion and slip flow were taken into account through the incorporation of apparent permeability. In their work, a shale reservoir was represented by the quadruple-porosity system which was first introduced by Aguilera (2010) and Andrade et al (2010Andrade et al ( , 2011, namely, as organic and inorganic matrix and natural and hydraulic fractures. Hudson (2011) analyzed the gas transport in shale reservoirs with an explicit differential model.…”
Section: Triple Porosity Methodsmentioning
confidence: 99%
“…Knudson diffusion and slip flow were taken into account through the incorporation of apparent permeability. In their work, a shale reservoir was represented by the quadruple-porosity system which was first introduced by Aguilera (2010) and Andrade et al (2010Andrade et al ( , 2011, namely, as organic and inorganic matrix and natural and hydraulic fractures. Hudson (2011) analyzed the gas transport in shale reservoirs with an explicit differential model.…”
Section: Triple Porosity Methodsmentioning
confidence: 99%
“…Reservoir simulation tools (Shabro 2011, Andrade 2011 are only now starting to incorporate some of these more complex flow models and the multi-component characteristics of these source rocks. Much of this knowledge is gained through a much deeper understanding of the basin modeling and source rock modeling disciplines.…”
Section: Basin Modeling and Source Rock Modelingmentioning
confidence: 99%
“…More recently, Fung et al (2011) have demonstrated applications with Middle Eastern carbonates of up to three porosity types within their generalized multi-porosity scheme. Moreover, interest in the simultaneous simulation of four porosity types for unconventional gas reservoirs is now under active study (Andrade et al 2011). This paper presents the design of our simulator with respect to the challenges of modeling multiple porosity types.…”
mentioning
confidence: 99%